Blood film examination for vacuolated lymphocytes in the diagnosis of metabolic disorders; retrospective experience of more than 2500 cases from a single centre. Issue 12 (25th November 2005) - Anderson, G; Smith, V V; Malone, M; Sebire, N J
Abstract : Background: A range of metabolic diseases can result in abnormal accumulation of metabolic byproducts, resulting in abnormal lymphocyte cytoplasmic vacuolation, identifiable on routine blood film examination. Aims: This study retrospectively examines the usefulness of blood film examination for vacuolated lymphocytes in a specialist paediatric pathology department in relation to patient's age and presentation. It also describes specific diagnostic features in relation to specific classes of metabolic disease. Methods: Retrospective review of a histopathology database to identify all blood films examined for the detection of vacuolated lymphocytes during a 15 year period (1989–2004). Results: In total, 2550 blood films were investigated. The median age at submission was 2 years (range, birth to 88), and > 90% of samples were from children < 18 years. The most common indications were developmental delay/regression, ataxia, seizures, and cardiomyopathy. Vacuolated lymphocytes were identified in 156 films (6.1%). The frequency of vacuolated lymphocytes varied with clinical presentation, with ophthalmic indications having the highest positive rate (40%). In cases with vacuolated lymphocytes, a wide range of underlying metabolic diagnoses was apparent, the most common being juvenile neuronal ceroid lipofuscinosis and acid maltase deficiency, which accounted for more than half of the diagnoses. Conclusions: The examination of blood films for lymphocyte vacuolation is clinically useful in patients with a history suggestive of metabolic disease. The test is cheap, rapid, minimally invasive, and provides first line screening, with some findings indicating clues to a specific underlying diagnosis.